OP0267 Sirt1 Regulates Canonical Tgf-Beta Signaling to Control Fibroblast Activation and Tissue Fibrosis. (10th June 2014) - Zerr, P.; Palumbo-Zerr, K.; Huang, J.; Distler, A.; Distler, O.; Schett, G.; Distler, J.H.
Abstract : Background: SIRT1 is a member of the sirtuin family (SIRT1-7) of proteins, homologs of the Sir2 in yeast. Sirtuins are characterized by a sirtuin core domain and grouped into four classes. SIRT1 is a class III histone deacetylase with important regulatory roles in transcription, cellular differentiation, proliferation and metabolism. Objectives: Considering that various epigenetic modifications have recently been linked to the pathogenesis of SSc, we aimed to investigate the role of SIRT1 in fibroblast activation and tissue fibrosis in SSc. Methods: SIRT1 expression was analyzed by real-time PCR, Western Blot and immunohistochemistry in cultured human fibroblasts, in murine models of SSc and in skin samples from SSc patients. Collagen synthesis was quantified by real-time PCR, SirCol- and hydroxyproline assays. The effects of SIRT1 on canonical TGF-β signaling were evaluated by Smad reporter assays and analyses of TGF-β target genes. SIRT1 signaling was modulated by SIRT1 agonist resveratrol and by fibroblast-specific knockout. The role of SIRT1 was evaluated in bleomycin-induced skin fibrosis in mice overexpressing a constitutively active TGF-β receptor I (TBR). Results: SIRT1 expression was decreased in the skin of SSc patients. IHC demonstrated a pronounced decrease of SIRT1 in fibroblasts in SSc skin. SIRT1 mRNA and protein levels were also decreased in bleomycin or TBR-induced skin fibrosis. TGF-β reduced mRNA and protein levels of SIRT1 in cultured fibroblasts. TBR overexpression reduced SIRT1 in murine skin, whereas treatment with the TBR inhibitor SD-208 prevented the downregulation of SIRT1 in experimental fibrosis. Activation of SIRT1 by treatment with resveratrol potentiated the stimulatory effects of TGF-β on cultured fibroblasts with more pronounced increases of Col1a1 mRNA and collagen protein. These effects were mediated by enhanced canonical TGF-β signaling as resveratrol induced SMAD-dependent transcription in reporter assays and increased the mRNA levels of CTGF of classical SMAD target genes. In contrast, knockdown of SIRT1 inhibited TGF-β/SMAD signaling and reduced release of collagen in fibroblasts. Consistent with a pro-fibrotic role of SIRT1, mice treated with resveratrol were more sensitive to bleomycin-induced dermal fibrosis with more pronounced dermal thickening (74%, p=0.006), increased myofibroblast counts and higher hydroxyproline levels. Mice with fibroblast-specific SIRT1 knockdown were less susceptible to bleomycin induced fibrosis. SIRT1 Inactivation also protected from fibrosis induced by overexpression of TBR. Conclusions: We identify SIRT1 as a crucial regulator of TGF-β/Smad signaling in SSc. Although SIRT1 is downregulated, this decrease is not sufficient to counter-balance the excessive activation of TGF-β signaling in SSc. However, augmentation of this endogenous regulatory mechanism, e.g. by knockdown of SIRT1 can effectively inhibit TGF-β signaling and exerts potent anti-fibrotic effects. Although further studies are required, these findings provide first evidence that SIRT1 may be an interesting target for pharmacological intervention. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2212